Evaluation of postoperative pain in felines undergoing ovariohysterectomy and orchiectomy - Muñoz-Rodríguez, Luis (2020)
The aim of this study was to assess postoperative pain from elective ovariohysterectomy or orchiectomy surgery in 66 felines (41 females and 25 males), using the UNESP-Botucatu multidimensional pain scale with emphasis on subscale 1 and 2. The analgesic protocol used included meloxicam 0.05 mg/kg and tramadol 3 mg/kg plus ketamine 10 mg/kg IV induction and maintenance at 5 mg/kg. The evaluation was carried out when the felines were without anesthetic effect and could reliably manifest behavioral disturbances indicative of pain associated with surgery. Pain assessments were conducted by two observers. The results showed that 89.4% of patients presented mild postoperative pain and 10.6% moderate pain. Moreover, 87.8% of females (36/41) and 92% of males (23/25) showed mild pain. None showed severe pain. The use of multidimensional scales like UNESP-Botucatu are key to adjust post-surgical analgesia needs in cats in spay and neuter programs.